Evaluation of damage performance in offshore floating photovoltaics-based hydrogen production system due to potential hydrogen release - Wang, Hao; Wang, Kan; Liu, Xiaolei; Liu, Yang; Qian, Zhijia; Ding, Sheng (Frontiers in Marine Science, 2024)
Green hydrogen is an important future energy source, which offers a vast potential to implement the decarbonization of the marine sector and advance broad shift to clean-energy alternatives globally. There are various advantages of offshore floating photovoltaics (FPVs) technology for hydrogen production; however, hydrogen storage in FPVs-based hydrogen production system faces several challenges. It is found that the major barrier concerning the system under investigation is related to safety. The current study aims to present an applicable offshore FPVs-based hydrogen production system, which involves both the FPV section and the hydrogen production section based on a project in China. A numerical 3D model is performed to investigate the characteristics of accidental damage through potential hydrogen storage device failure during system operation. The hydrogen release process of an FPVs-based hydrogen production system is presented with different offshore wind conditions, and the parameters for understanding the motion state and hydrogen release mode of hydrogen are also analyzed. The study further explores the dynamic development of hydrogen dispersion from a hydrogen production platform, including a momentum-dominated region, a horizontal spreading region, and a vertical buoyancy region. In addition, the influence of hydrogen explosive flame on thermal damage evaluation is illustrated, and thermal hazards under different offshore wind conditions are also discussed. The current study contributes to a better understanding of failure analysis of the FPVs–hydrogen production system and elaborates on damage evolution of hydrogen storage integrated with the system. The study also concentrates on marine environmental synergistic limits considering thermally damaged mechanical properties.